An enquiry into the causes of an explosion accident occurred in a biogas plant. Issue 1 (30th May 2019) - Boscolo, Marco; Bregant, Luigi; Miani, Stefano; Padoano, Elio; Piller, Marzio
Abstract: Biogas is a versatile carrier of renewable energy produced by means of the digestion of crops, residues, or other wastes, and storage of the gas in dedicated plants. Safety regulations impose operational and technical restrictions to areas interested by the presence of the biogas in order to limit the explosion risk. Conversely, other areas of the plant are not subject to strict safety requirements. Nevertheless, explosions can be triggered in these areas as well, as the present investigation confirms. In the specific case, the production of biogas by anaerobic digestion in a storm‐water tank and its infiltration and accumulation into a technical building through a pipe connection caused the explosion of the building itself. The authors describe the procedures adopted for the enquiry and suggest possible improvements to the safety regulations for biogas plants.